Surface Brillouin scattering studies of elastic properties of materials at high temperature - Mathe, Bhekumusa Abraham (My University, 2009)
Brillouin scattering from surfaces, more often called surface Brillouin scattering (SBS) has been widely used to investigate elastic properties of thin films, interfaces, layered systems. In this thesis, the focus is on bulk specimens, ranging from large oriented crystals to polycrystalline layers. Well-characterised titanium alloys (TiC and TiCN) are shown to have elastic moduli that obey the quasi-harmonic approximation while retaining their refractory properties. Iron (IV) sulphide, is investigated at ambient and high temperatures where it is demonstrated that the elastic constant C12 has a positive value even at high temperatures, and comparison of the high temperature elastic constants data to theoretical results obtained from models developed by Sithole et. al. shows reasonably good agreement. An amorphous boron carbide film deposited on silicon is shown to undergo a phase change at about 350 - 400oC to a possibly nanocrystalline state, a process that is accompanied by an increase in Young’s modulus of about 14 GPa from ambient value. The combination of SBS dispersion results and Green’s function analysis of organ-pipe modes observed for the boron carbide film, has the potential of being used to extract elastic constants of thin layers, where appropriate conditions for the observation of these modes are met by the layer/substrate system. An agreement to within 6% between elastic moduli determined using SAWs and with those extracted from organ-pipe modes demonstrates the applicability of this approach to the analysis of some layered systems. Boron-doped polycrystalline silicon (polysilicon in short) is a popular MEMS structural material, and high temperature measurements of this material are reported for the first time for the temperature range beyond 100oC where the Young’s moduli is observed to remain consistent at about 163 GPa. The increase in bulk modulus observed at about 300oC is associated with growth of crystallites as a result of the very long thermal-soaking periods. High temperature Raman measurements conducted parallel to the SBS measurements show an unusual recovery of the asymmetry of the Fano-line shape on cooling down to room temperature. Grain boundary diffusion of the smaller boron atoms and lattice relaxation effects are considered to explain the phenomenon, and the results are related to the corresponding SBS elasticity measurements.